2006
DOI: 10.1093/ndt/gfl250
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular paclitaxel wraps block arteriovenous graft stenosis in a pig model

Abstract: Our results demonstrate the safety and efficacy of paclitaxel-loaded perivascular wraps in the setting of a pig model of arteriovenous graft stenosis. We believe that such a local approach which could be easily applied at the time of surgery is ideally suited for use in the clinical setting of haemodialysis vascular access dysfunction. It is likely that this novel approach could result in a significant reduction in the huge economic and health morbidity costs currently associated with this recalcitrant clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 27 publications
0
52
0
Order By: Relevance
“…Perivascular delivery of antiproliferative drugs permits achieving high local drug levels while avoiding systemic toxicity. Two studies using a porcine arteriovenous graft model demonstrated reduction of neointimal hyperplasia and graft stenosis by perivascular delivery of paclitaxel (95,96). No human studies have been reported to date using local drug delivery systems to prevent graft failure.…”
Section: Pharmacologic Interventions To Reduce Graft Thrombosismentioning
confidence: 99%
“…Perivascular delivery of antiproliferative drugs permits achieving high local drug levels while avoiding systemic toxicity. Two studies using a porcine arteriovenous graft model demonstrated reduction of neointimal hyperplasia and graft stenosis by perivascular delivery of paclitaxel (95,96). No human studies have been reported to date using local drug delivery systems to prevent graft failure.…”
Section: Pharmacologic Interventions To Reduce Graft Thrombosismentioning
confidence: 99%
“…Biodegradable polymer wraps have been used to deliver antiproliferative drugs to the perivascular region of hemodialysis access vessels in both animal models (70) and patients. In animal studies, perivascular wraps that elute paclitaxel were beneficial in inhibiting neointimal hyperplasia in AVGs (71). The paclitaxel wrap combination (Vascular Wrap; Angiotech) was shown to be beneficial in preventing neointimal hyperplasia in peripheral arterial bypass grafts in a European cohort.…”
Section: Perivascular Approachesmentioning
confidence: 99%
“…However, the arteries had incomplete healing of the endothelium, increased numbers of inflammatory cells, and extensive fibrin and platelet deposition [233,[235][236][237]. In pigs, paclitaxel given locally via an arterial stent or administered locally to vein grafts or arteriovenous shunts resulted in reduced neointimal formation in the short term [98,233,238], but this benefit was not seen in longer term experiments due to "catch-up" neointimal formation [98,233]. Other means of delivering paclitaxel have been investigated, including encapsulating it in multilayered "nanoburrs" that have hooks on their surface that bind to specific peptides on exposed surfaces.…”
Section: Cytostatic and Immunosuppressivementioning
confidence: 99%